STRATEGI PEMBELAJARAN SENI LUKIS ANAK USIA DINI DI SANGGAR PRATISTA YOGYAKARTA - Tri Hartiti Retnowati (FBS UNY, 2009)
The aim of this study are to know instructional strategy on painting art for pre-schooler children at Sanggar Pratista Yogyakarta. The subjects on this study are pre-schooler children and the teacher who follow the actvity at this place. The data get by using observation, interview, and documentation. The data were analyzed by using descriptive approach on two step. The first step analyzed data has been done during collected data from observation, interview, and documentation. All the data were reducted to get the main information that will be used on this study. The second step all the main information that get from first step were served reguraly to make conclution about this study. The finding show that the instructional stategy on painting art for pre-schooler children used indivually instructional model with giving examples method. The purpose of giving examples was to give early model and than the children has to continue the examples that has been given by the teacher. The giving examples method was effective to motivate children on expressing skill, coloring skill, and find new object on their painting. Keywords: instructional strategy, giving examples method, indivually instructional model